Government Policy Strategies of Bandar Lampung City in Reducing School Dropout Rates - Indah Wulan Sari (Jurnal Kebijakan Publik, 2025)
The phenomenon of school dropouts in Bandar Lampung City is still a serious problem that hinders the achievement of the 13-Year Compulsory Learning program and has the potential to widen the socio-economic gap of the community. This problem stems from three main dimensions, namely economic factors for families who are unable to bear the cost of indirect education, limited access due to limited public school capacity and high private school costs, and weak institutional governance related to data integration, early detection, and monitoring-evaluation systems. This policy paper aims to analyze the root of the problem of school dropout in Bandar Lampung City while offering a comprehensive, realistic, and sustainable policy strategy. The analysis method used is a policy analysis framework with stages of problem identification, mapping of policy options, evaluating the advantages and disadvantages of each option, and formulating strategic recommendations. The results of the analysis show that the most effective strategy is a combination of policy mix in the form of quick interventions to reduce the current dropout rate, improved governance through data integration and strengthening the Early Warning System (EWS), and expanding access to education through collaboration with private schools, CSR, and philanthropic institutions. Legal instruments in the form of the Mayor's Regulation (Perwali) on Coping with School Dropout and the 13-Year Compulsory Learning Transition Guarantee are needed as a strong legal basis for the implementation of policies. In addition, the establishment of an Anti-School Dropout Task Force (STAPS) is recommended to ensure coordination across OPDs, policy synchronization, and acceleration of decision-making in handling cases of vulnerable students. In conclusion, the policy to alleviate school dropouts in Bandar Lampung City must be implemented in an integrated, data-based, and multi-stakeholder manner. With this strategy, it is hoped that the dropout rate can be reduced by at least 30% in two years, the transition rate of junior high school → high school/vocational school will increase by ≥10 percentage points, and a more inclusive, adaptive, and sustainable city education governance will be built.